Coisa julgada e os limites objetivos sobre as questões prejudiciais no Código de Processo Civil de 2015 - Assis, Gabriel Zoboli de (2019)
The aim of the present work is to bring reflection on the institute of the res judicata, mainly by procedural innovation about its incidence on issue preclusion. Thus, to answer if this extension of the objective limits of res judicata, in view of the changes in the Code of Civil Procedure of 2015 in comparison to that of 1973, meets the paradigms of predictability, efficiency, stability, coherence and integrity. And, through this transformation context, to question whether the institute of res judicata - as outlined dogmatically by the Brazilian law order - and its objective limits on the issue preclusion satisfy, simultaneously and concomitantly, the principles of effectiveness and legal certainty.